2016
DOI: 10.1179/1351000215y.0000000027
|View full text |Cite
|
Sign up to set email alerts
|

Thiol/disulfide homeostasis: A prognostic biomarker for patients with advanced non-small cell lung cancer?

Abstract: These results suggest that in advanced stage NSCLC, the native thiol, total thiol, and disulfide levels decrease, while the native thiol/disulfide ratio does not change. Low levels of thiol/disulfide parameters are related to tumor aggressiveness and may predict a poor outcome for patients with NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
73
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 31 publications
6
73
3
1
Order By: Relevance
“…In their preliminary studies, they reported that increased thiol and decreased disulphide levels were associated with proliferated diseases, such as multiple myeloma and malignancies, whereas decreased thiol levels and increased disulphide levels were associated with degenerative diseases, such as diabetes, obesity, pneumonia and smoking. [30][31][32] However, our results showed that dynamic thiol disulphide homeostasis is associated with an increased shift to the reductive side as a proliferative manner, in women diagnosed with major depressive disorder. In our correlation analysis, we found a negative correlation between depression severity and plasma disulphide levels only in the patient group.…”
Section: Anadolu Psikiyatri Derg 2018; 19(2):135-142contrasting
confidence: 47%
“…In their preliminary studies, they reported that increased thiol and decreased disulphide levels were associated with proliferated diseases, such as multiple myeloma and malignancies, whereas decreased thiol levels and increased disulphide levels were associated with degenerative diseases, such as diabetes, obesity, pneumonia and smoking. [30][31][32] However, our results showed that dynamic thiol disulphide homeostasis is associated with an increased shift to the reductive side as a proliferative manner, in women diagnosed with major depressive disorder. In our correlation analysis, we found a negative correlation between depression severity and plasma disulphide levels only in the patient group.…”
Section: Anadolu Psikiyatri Derg 2018; 19(2):135-142contrasting
confidence: 47%
“…In their preliminary studies, they showed that plasma disulphide levels were higher in patients with degenerative diseases, such as diabetes, smoking, obesity, and pneumonia, and were lower in patients with proliferative diseases, such as multiple myeloma, colon cancer, and renal cancer. [36][37][38] We found lower disulphide levels in patients with FMS compared with the healthy controls. However, we did not observe any difference in total thiol levels between the two groups.…”
Section: Discussionmentioning
confidence: 59%
“…Oxidative stress has attracted the interest of clinicians for a long time and it has been shown that it has a critical role in the progress of various diseases such as type 1 diabetes mellitus, cancer, atherosclerosis, and hypertension. [21][22][23][24] Both excessive oxidative stress and inadequate defence of cardiomyocytes can also play a role in the development of early onset of chemotherapy-induced cardiotoxicity. 3) Myocardial cells, a metabolically active tissue, have an elegant system of antioxidant defenses and cell repair mechanisms against oxidative and nitrosative stress which can cause cell necrosis and/or apoptosis.…”
Section: Discussionmentioning
confidence: 99%